Impact of Media-Based Negative and Positive Age Stereotypes on Older Individuals' Mental Health. (8th May 2021) - Levy, Becca R; Chang, E-Shien; Lowe, Sarah R; Provolo, Natalia; Slade, Martin D
Abstract: Objectives: During the COVID-19 pandemic, stigmatization of older persons increased in traditional and social media. It was unknown whether this negative messaging could be detrimental to the mental health of older individuals, and whether the relatively uncommon positive messaging about older individuals could benefit their mental health. Method: To address these gaps, we designed age-stereotype interventions based on actual news stories that appeared during the pandemic, and divided them into negative and positive versions of what we term personified (i.e., individual-based) and enumerative (i.e., number-based) age-stereotype messaging. The negative versions of the 2 types of messaging reflected the age stereotype of decline, whereas the positive versions of the 2 types of messaging reflected the age stereotype of resilience. Results: As expected, the exposure of older individuals to the negative-age-stereotype-messaging interventions led to significantly worse mental health (i.e., more anxiety and less peacefulness), compared to a neutral condition; in contrast, the positive-age-stereotype-messaging interventions led to significantly better mental health (i.e., less anxiety and more peacefulness), compared to a neutral condition. The findings were equally strong for the personified and enumerative conditions. Also as expected, the interventions, which were self-irrelevant to the younger participants, did not significantly impact their mental health. Discussion: This is the first-known study to experimentally demonstrate that institutional ageism, and statistics that reflect stereotypes about older individuals, can impact mental health. The results demonstrate the need for media messaging aimed at empowering older individuals during the pandemic and beyond.